Sintesis Produksi Puisi oleh Kecerdasan Buatan: Keterbatasan Fungsi Simbol dan Tanda Perspektif Semiotika Roland Barthes - Lestari, Citra Rizky (TRANSFORMATIKA, 2024)
In recent years, the rapid development of Artificial Intelligence has significantly impacted various aspects of life, including the realm of creative writing in literature. One prominent application of AI is ChatGPT, which can synthesize poetry. However, questions have arisen regarding the extent of their ability to understand and replicate symbolic and sign meanings in literary works, particularly in poetry. This research aims to explore the intervention of artificial intelligence in the poetry creation process and identify limitations related to the use of symbolic and sign functions. Utilizing the perspective of Roland Barthes' Semiotics, this study delves into the symbolic meanings in poetry. The research employs a qualitative descriptive method with hermeneutic reading and content analysis of poetry, comparing it with human-authored poetry. The research data consists of poetry created by the artificial intelligence ChatGPT and human-authored poetry. The results indicate limitations in the ability of artificial intelligence to use symbols and signs in poetry, resulting in interpretations that are limited and tend to follow conventional patterns. Artificial intelligence often relies on common symbols and signs, frequently associated with existing cultural myths. Therefore, the role of humans in the creative process remains crucial in literary writing to ensure the diversity of symbols and signs, fostering the development of more innovative and profound interpretations in poetry.